Motivação: um enfoque neurofisiológico - Fernandes, Leda Maria Sebrão (1976)
Do not forgetting all social a social Corporation that is implicitly connected with the MOTIVATION, the objective of presente work is its study in neurophysiological bases. We know that motivation still does not have solidified its 'constructum'. It has a variability of understanding from psychological school to psychological school, from researcher to researcher, from culture to culture, from time to time… This work doesn not have the reductionist goal in which we just see the motivation with neurophysiological bases. Its objective is to clear up a so controvertible field. We can see that in spite of the many ways to look upon motivation as a social process, its way of happen, physiologically, can be more delimited. Whatever the concept given to motivation, it has an undeniable inner physiological mechanism, and I will work in this field. What happens in the nervous system when an alive being is motivated? Is the physiological mechanism different from one being to another? Or is different only fro species to species? We will begin our work looking to the different views of motivetion and how the scientists regard it. We can note that the preoccupation in establishing a starting point more operational to the development of the physiology in scientifical bases has been existing for e long time. To this FUNKENSTEIN, CANNON, SHERRINGTON, MAGOUN e MORUZZI, SECHENON, LASHLEY and others have given a great contribution. Nevertheless, firstly this preoccupation was for the behavior visceral and somatical manifestations. Only with the development of the researchings on the Hypothalamus and limbic System we cauld really got a bot get field to the motivation research. We can forget the contributions of SKINNER and PAVLON about recompense. Or BANDURA with the variable – behavior modelling. Or BUTTLER and NISSEN with the description of the behavior of exploratory curicsity. Or HERB with the effects of restrict sensorial simulation. Or JAMES OLDS with the electrical stimulation… We’ll study the recent theoretical interpretations of CANNON, LASHlEY, BEACH, MORGAN, LORENZ, DEUTSCH, LIDSLEY, GROSSMAN. We'll make anatomical, histological and physlological considerations, connections are functions in the study of the Limbic System and its components. Our greatest preoccupation will be in trying to explain motivational mechanisms, their relation with the nervous System. We’ll study sexual, hunger, thirst, pain, motherly end fatherly, defense, attack OI' comination motivations, and how they are connected to the Nervous System. For this we’ll present experiences made on the sersorial motivation and emotion, and the experience of OLDS on the motivational factors gotten through stimulations or ablations of certain aress of the Limbic System. I hope that with this work I can contribute e little for a son great field of study.